Luminescent and magnetic properties of cerium-doped yttrium aluminum garnet and yttrium iron garnet composites. Issue 8 (1st June 2019) - Jung, Hyun Kyu; Kim, Chang Hee; Hong, A-Ra; Lee, Seung Han; Kim, Tae Cheol; Jang, Ho Seong; Kim, Dong Hun
Abstract: Functional materials exhibiting magnetic and luminescent properties have been recognized as an emerging class of materials with great potential in advanced applications. Herein, properties of multifunctional ceramic composites consisting of two garnets, luminescent cerium-doped Y3 Al5 O12 (Ce:YAG) and magnetic Y3 Fe5 O12 (YIG), are reported. On increasing the sintering temperature, both the photoluminescence and saturation magnetization of the Ce:YAG-YIG composites decreased gradually because of the interdiffusion of trivalent ions such as Al 3+ and Fe 3+ . At a constant sintering temperature of 1100 °C, the YIG contents in the composites increased, thereby causing their luminescent properties to degrade and the saturation magnetizations to increase. For application to electronics, Ce:YAG-YIG composite thin films were integrated on quartz substrates by sputtering the ceramic target. The composite thin films exhibited both magnetic and luminescent properties after annealing. These techniques facilitate the incorporation of multifunctional nanocomposites into various devices.